Coping with Interference in Wireless Networks - Kazemitabar, Seyed Javad; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2011)
Unlike wired networks where transmitters have no effect on receivers other than their own, in wireless networks we are limited by interference. The traditional routing methods are not optimal any more when it comes to a wireless medium. The maximum data rate on each link depends not only on the power in that link but also on the transmitted power from adjacent links. That is why the problem of power optimal routing needs to be solved jointly with scheduling. This suggests a cross layer design method as opposed to traditional networking where the algorithm for each layer is designed separately. In Coping with Interference in Wireless Networks we introduce several methods engaging different layers of network to mitigate interference in a wireless network.
Dedication -- List of Figures -- List of Tables -- Foreword -- Preface -- Acknowledgements -- 1 Introduction -- 2 Multi-User Communication and Interference Cancellation -- 3 Diversity Analysis of Multiple-Antenna Multi-User Systems -- 4 Global Optimal Routing, Scheduling and Power Control for Multi-hop Wireless Networks with Interference -- 5 Connectivity in Wireless Networks -- References -- Index.
Keywords: Engineering; Computer Communication Networks; Telecommunication; Engineering; Communications Engineering, Networks; Computer Communication Networks